Clinical Features and Efficacy of Benralizumab in Patients with Blood Eosinophil Count Between 300 and 450 Cells/mm3: A Post Hoc Analysis from the ANANKE Study - Senna G; Aliani M; Altieri E; Bracciale P; Brussino L; Caiaffa MF; Cameli P; Canonica GW; Caruso C; D'Amato M; De Michele F; Del Giacco S; et al. (Journal of Asthma and Allergy, 2022)
Gianenrico Senna,1,2 Maria Aliani,3 Elena Altieri,4 Pietro Bracciale,5 Luisa Brussino,6 Maria Filomena Caiaffa,7 Paolo Cameli,8 Giorgio Walter Canonica,9,10 Cristiano Caruso,11 Maria D’Amato,12 Fausto De Michele,13 Stefano Del Giacco,14 Fabiano Di Marco,15 Francesco Menzella,16 Girolamo Pelaia,17 Paola Rogliani,18,19 Micaela Romagnoli,20 Pietro Schino,21 Jan Walter Schroeder,22 Alessandra Vultaggio,23 Sara Rizzoli,24 Alessandro Zullo,24 Silvia Boarino,25 Marilena Palmisano,26 Alessandra Rossi,26 Gianfranco Vitiello,26 Stefano Centanni27 1Department of Medicine, University of Verona, Verona, Italy; 2Allergy Unit and Asthma Center, Verona University Hospital, Verona, Italy; 3UO Pneumologia e Pneumologia Riabilitativa, ICS Maugeri, IRCCS Bari, Bari, Italy; 4Reparto di Pneumologia, P.O., Garbagnate Milanese, Italy; 5Reparto di Pneumologia, Ospedale Ostuni, Ostuni, BR, Italy; 6Dipartimento di Scienze Mediche, SSDDU Allergologia e Immunologia Clinica, Università degli Studi di Torino, AO Ordine Mauriziano Umberto I, Torino, Italy; 7Cattedra e Scuola di Allergologia e Immunologia Clinica, Dipartimento di Scienze Mediche, Università di Foggia, Foggia, Italy; 8Respiratory Diseases and Lung Transplantation, Department of Medical and Surgical Sciences & Neurosciences, Siena University Hospital, Siena, Italy; 9Department of Biomedical Sciences, Humanitas University, Pieve Emanuele, MI, Italy; 10Personalized Medicine Center: Asthma and Allergology, Humanitas Research Hospital, Rozzano, MI, Italy; 11Dipartimento di Scienze Mediche e Chirurgiche, Fondazione Policlinico A. Gemelli, IRCCS, Università Cattolica del Sacro Cuore, Roma, Italy; 12UOSD Malattie Respiratorie “Federico II”, Ospedale Monaldi, AO Dei Colli, Napoli, Italy; 13UOC Pneumologia e Fisiopatologia Respiratoria, AORN A. Cardarelli, Napoli, Italy; 14Department of Medical Sciences and Public Health, University of Cagliari, Cagliari, Italy; 15Department of Health Sciences, Università Degli Studi Di Milano, Pneumologia, ASST Papa Giovanni XXIII, Bergamo, Italy; 16UOC Pneumologia, Ospedale “S. Valentino”, AULSS 2 Marca Trevigiana, Montebelluna, TV, Italy; 17Dipartimento di Scienze della Salute, Università Magna Graecia, Catanzaro, Italy; 18Division of Respiratory Medicine, University Hospital “Tor Vergata”, Roma, Italy; 19Unit of Respiratory Medicine, Department of Experimental Medicine, University of Rome “Tor Vergata”, Roma, Italy; 20UOC Pneumologia, ULSS 2 Marca Trevigiana, Treviso, Italy; 21Fisiopatologia Respiratoria, Ospedale Generale Regionale, Ente Ecclesiastico “F. Miulli”, Acquaviva delle Fonti, BA, Italy; 22Allergy and Clinical Immunology, ASST Grande Ospedale Metropolitano Niguarda, Milano, Italy; 23Dipartimento di Medicina Sperimentale e Clinica, Università degli Studi di Firenze, Firenze, Italy; 24Medineos Observational Research - An IQVIA Company, Modena, Italy; 25Medical Evidence R&I, AstraZeneca, Milano, Italy; 26Medical Affairs R&I, AstraZeneca, Milano, Italy; 27Respiratory Unit, ASST Santi Paolo e Carlo, Department of Health Sciences, Università degli Studi di Milano, Milano, ItalyCorrespondence: Marilena Palmisano, Medical Affairs R&I, AstraZeneca, Milano, Italy, Email marilena.palmisano@astrazeneca.comPurpose: Benralizumab effectively reduces severe eosinophilic asthma (SEA) exacerbations in patients with a wide range of baseline blood eosinophil count (BEC). Patients included in real-world studies are often characterized by high mean/median BEC, while patients with BEC close to 300 cells/mm3 are poorly represented. This post hoc analysis from the Italian study ANANKE aims to define the clinical features and corroborate the efficacy of benralizumab in real world in the BEC 300– 450 cells/mm3 subset of patients.Patients and Methods: Post hoc analysis of the Italian, multicenter, observational, retrospective real-life study ANANKE (NCT04272463). Baseline clinical and laboratory characteristics were collected in the 12 months prior to benralizumab treatment and presented for a BEC 300– 450 cells/mm3 subgroup of patients. Change over time of BEC, annualized exacerbation rate (AER), asthma control (ACT), lung function and oral corticosteroid (OCS) use at 16, 24 and 48 weeks after benralizumab introduction were collected.Results: A total of 164 patients were analyzed, 34 of whom with a BEC of 300– 450 cells/mm3. This subgroup was more likely to be female (64.7%), with lower rates of severe exacerbations at baseline when compared to the total population (0.69 vs 1.01). After 48 weeks of benralizumab treatment, the BEC 300– 450 subset showed similar reductions in AER (− 94.8% vs − 92.2%) and OCS use (median dose reduction of 100% in both groups), as well as improvement in ACT score (median scores 22.5 vs 22) and lung function (pre-BD FEV1: +200 mL vs +300 mL) when compared to the total population. No discontinuations for safety reasons were registered.Conclusion: At baseline, apart from lower severe exacerbation rate, the BEC 300– 450 cells/mm3 subset of patients is comparable to the total population prescribed with benralizumab. In this real-life study, benralizumab is as effective in BEC 300– 450 patients as in the total population.Keywords: severe eosinophilic asthma, blood eosinophil count, benralizumab, observational, real-world evidence, real-life